Factors Of Achieving Pressure Affect Stress In School Children In Batu City Region - Rita Yulifah (poltekkes kemenkes mataram, 2020)
Stress is a condition that occurs in everyday life. In the life cycle stress can occur in adults and school-age children. Of the 40% population consisting of children and adolescents, 7-14% of children experience mental health problems, namely hyperactivity to learning difficulties. Stress that occurs in school-age children is stress that comes from the learning process or things related to pressure, especially the pressure before the final exam (State exam). The study is a descriptive analytic study with a cross sectional approach which aims to formulate the factors that influence the emergence of stress in school-age children in the Batu City area. The population of sixth grade elementary school students was 195 people taken by proportional random sampling. Data were analyzed using logistic regression. The results showed that there were 4 stressful factors in school-age children, namely 89.2% pressure factors for achievement, 38.5% pressure factors to compete in graduation, 24.6% pressure factors to be accepted, and 53.3% factor in many activities before the final exam. The results of the analysis using logistic regression found an overall value of 67.69%, indicating that based on the pressure for achievement, competing, accepted and many activities from 195 respondents the possibility of an estimate for stress was 67.69%. The implications of the results of these studies can be taken into consideration by parents and educators should not be too demanding for children to achieve high achievement standards, not stressing to always be at the top. Learning is adapted to children's rights and continues to pay attention to the needs of children, so that children can achieve achievements in school, continuing their growth and development.